Robot-assisted versus open radical nephroureterectomy for urothelial carcinoma of the upper urinary tract: A retrospective cohort study across ten years. (September 2021) - Zeuschner, Philip; Vollmer, Sarah Grosse; Linxweiler, Johannes; Wagenpfeil, Gudrun; Wagenpfeil, Stefan; Saar, Matthias; Siemer, Stefan; Stöckle, Michael; Heinzelbecker, Julia
Abstract: Purpose: Radical nephroureterectomy is the gold standard of treatment for high-risk non-metastatic urothelial carcinoma of the upper urinary tract. However, the optimal surgical approach remains a controversial debate. This study compared the perioperative and oncological outcomes of open and robot-assisted radical nephroureterectomies. Methods: 131 consecutive radical nephroureterectomies (66 robot-assisted nephroureterectomies vs. 65 open nephroureterectomies) for urothelial carcinoma of the upper urinary tract at a single tertiary referral center were included from 2009 to 2019. The perioperative and oncological outcomes were compared between both surgical approaches, including logistic regression analysis, propensity score matching, Kaplan Meier analyses, and Cox regression models. Results: Overall, robot-assisted surgery had less blood loss (150 ml vs. 250, p = 0.004) and less positive surgical margins (1.5% vs. 15.4%, p = 0.004) at a comparable operating time (robotic 188min vs. 178). Any grade complications were more frequent after open surgery (40.9% vs. 63.1%, p = 0.011), and the length of stay was shorter after robotic nephroureterectomy (9 days vs. 12, p < 0.001). These differences remained significant in the propensity score matched analysis, except for the complication rates, which were still lower for the robotic approach, but no longer significant. At a median follow-up of 30.9 months (range 1.4–129.5), neither the progression-free survival (PFS, 2-year: robotic 66.7% vs. open 55.3%), nor the overall survival differed significantly (OS, 2-year: robotic 76.2% vs. open 68.4%). In the Cox regression, the surgical approach did not impact the PFS or OS. Lymph node metastases (HR 3.32, p = 0.008) had the strongest impact on the PFS besides patient age (HR 1.51 per 10 years, p = 0.025) and prior cystectomy (HR 2.42, p = 0.026) in the multivariate analysis. Conclusions: Robot-assisted radical nephroureterectomy had significant perioperative advantages at comparable oncological outcomes compared to open surgery for the treatment of urothelial carcinoma of the upper urinary tract at a high volume center, experienced in robotic surgery. Highlights: We found perioperative advantages of robotic nephroureterectomy compared to open. The robotic approach has less blood loss, positive margins & shorter length of stay. These differences remained significant in the propensity score matched analysis. There was no evidence of atypical metastatic spread after robotic surgery. The oncological outcome was equivalent and not impacted by the surgical approach.